Variabilité des nutriments foliaires de Quercus suber L dans différentes situations écologiques dans le massif des Maures (Var, France), et relations avec la production de liège (Ann. For. Sci., 1996)
Variability of foliar nutrient contents of Quercus suber L in several ecological conditions in the Maures Mountains (Var, France), and relations with cork production. A monitoring of foliar nutrients has been undertaken on cork-oaks (Quercus suber L), in the Maures Mountains (Var, France). Simultaneously, the thickness of cork age rings has been studied to define the relationship of the cork production to nutrient contents under different ecological conditions. Foliar concentrations of ions evolved according to the season, the degradation state and the xericity of plots. Nitrogen appeared proportional to the physiological activity of the leaf, while calcium and potassium were stocked gradually. The calcium-magnesium antagonism was confirmed. Furthermore, changes of the nutrient concentrations in the undergrowth-clearing sites are reduced from the spring resumption of the metabolism. The growth of primary cork is linear with time, irrespective of year, climatic conditions and perturbations. The secondary (or reproductive) cork production is not linear with time and the age of trees, but it remains much higher than the primary cork production. The higher secondary cork productions are linked to the high contents of potassium and nitrogen, and to the moist and weakly disturbed plots. Magnesium is linked to small width thicknesses of cork age rings. Sodium and calcium do not appear to influence this cork production.